Strategi Pengembangan Objek Wisata Patung Palindo Di Desa Kolori Kecamatan Lore Barat Kabupaten Poso - Toheke, Ivana; Mufti, Mohammad Irfan; Haryono, Dandan (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This study aims to determine the development that has occurred at the Palindo Statue tourist attraction and to identify strategies for the development of the Palindo Statue tourist attraction. This research uses a qualitative method with a descriptive research type. The study applies the Development theory model (Hasibuan, 2005), which includes Human Resource Development, Performance Improvement, Systematic Processes, Active Participation, and Evaluation. Data collection was carried out through observation, interviews, and documentation, including both primary and secondary data.The results of the study indicate that the development at the Palindo Statue tourist attraction has not been optimal due to the lack of human resources in management, inadequate facilities and infrastructure, limited community participation in management, unstructured management practices, insufficient tourism promotion, budget constraints that limit management activities, and local government inefficiency in implementing policies related to tourism programs. Based on these findings, local governments, communities, and managers are expected to pay greater attention to these issues and implement better development strategies for the tourist attraction in the future. An aggressive (growth-oriented) strategy is considered the most appropriate and suitable strategy for developing the Palindo Statue tourist attraction.